(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2019)
This research deals with the culture of the family in the Arab society generally and in Syria in particular, in light of the historical origin of the contemporary family in the Arab Renaissance Era, exactly in the nineteenth century to the beginning of the twentieth century, which examines the social situation in that period of time, and the historical conditions that built the modern Arab family in that period, and the impact of that period of time in crystallizing the culture of the contemporary Arab family, so as to explain the characteristics of the Arab family and link them to their modern social origin.